2000
DOI: 10.2165/00002512-200016060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Medication Appropriateness in the Elderly

Abstract: The disproportionate use of medications, combined with age-related pharmacokinetic and pharmacodynamic changes, places older adults at high risk for medication related problems (MRPs). MRPs demonstrate significant morbidity, mortality and economic impact among healthcare systems. The negative outcomes associated with MRPs emphasise the need for more careful and thorough assessments of drug therapy among older adults. In the 1990s a number of methods and instruments were developed to assist in the assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 64 publications
0
46
0
4
Order By: Relevance
“…[10] Beers criteria are well established and very frequently used method for evaluating appropriateness of prescribing in elderly. It was developed in 1999 and revised in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Beers criteria are well established and very frequently used method for evaluating appropriateness of prescribing in elderly. It was developed in 1999 and revised in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hilmer et al suggested similar findings; increased exposure to medications with anticholinergic and sedative effects, measured through the Drug Burden Index (DBI), was found to be associated with lower physical function over a 5-year period in community-dwelling older adults [17]. These adverse effects are of significant concern in older adults because of polypharmacy, comorbidities and age-related changes in pharmacokinetic and pharmacodynamic parameters [18]. Drugs with significant anticholinergic side effects are thus generally considered potentially inappropriate and should be avoided in the older population irrespective of the diagnosis [19].…”
Section: Introductionmentioning
confidence: 86%
“…None of the currently available measurement tools cover all aspects of the aforementioned prescribing process. Nonetheless, several methods and instruments have been developed in order to assess prescribing, including whether guidelines are met in combination with the evaluation of the entire drug profile of individual patients [5]. The ideal instrument would be a combination of a structured approach together with a possibility to apply clinical judgment [5].…”
Section: Introductionmentioning
confidence: 99%